Improving the motor activity of highly qualified football players in China taking into account the variation of the intensity of training at small venues - Yaci, L.; Polishkis, M. M.; Pleshakov, A. A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to evaluate the effectiveness of the methodology for improving the motor activity of highly qualified female football players in China, taking into account the variation in the intensity of training at small venues.